2020
DOI: 10.1111/1346-8138.15693
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus‐like lesion preceding bullous pemphigoid development after programmed cell death protein‐1 inhibitor treatment

Abstract: Immune checkpoint inhibitors including programmed cell death protein 1 (PD‐1) antibody are used in major breakthrough therapies in cancer, however they cause unique adverse events, termed immune‐related adverse events (irAEs). Among the various dermatological irAEs, an autoimmune bullous disease, bullous pemphigoid (BP), the hallmarks of which are circulating autoantibodies to epidermal basement membrane zone (BMZ) including BP180, have been noted. However, the mechanism and timing of autoantibody production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…The vicious circle could be named epitope spreading. Similar phenomenon was also observed in ICIs-related bullous pemphigoid 10. In conclusion, we provided more evidence that anti-SSA antibody was found in TEN patients triggered by anti-PD1 therapy.…”
supporting
confidence: 86%
“…The vicious circle could be named epitope spreading. Similar phenomenon was also observed in ICIs-related bullous pemphigoid 10. In conclusion, we provided more evidence that anti-SSA antibody was found in TEN patients triggered by anti-PD1 therapy.…”
supporting
confidence: 86%
“…1 Recently, a few cases of LPP induced by pembrolizumab have been reported (Table S1). [2][3][4][5] Antibodies against BP180NC16a were detected in all previous cases, while antibodies against the C-terminal region of BP180 were detected in our case. There were no clinical differences between the above two types, but our patient had a good response to a small dose of oral steroid (PSL 10 mg/day).…”
Section: Dear Editorsupporting
confidence: 41%
“…Varying severities have been reported following PD‐1 inhibitors depending on concurrent treatment for underlying malignancy. 20 For instance, combinational therapy of radiation and nivolumab has resulted in multiple, erosive LP. The initial eruptions only became erosive after radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…While one previous report does indicate a LPP case following pembrolizumab, a separate study found this conclusion unlikely since clinical and histological findings lacked blisters of LP lesions. 20 In one case, an 87‐year‐old female with NSCLC was diagnosed with LPP following 9 cycles of nivolumab. Another case of a 57‐year‐old male with NSCLC had LPP after 3 months of nivolumab treatment.…”
Section: Discussionmentioning
confidence: 99%